BIOLOGICAL MECHANISMS AND TISSUE RESPONSE DURING ORTHODONTIC TOOTH MOVEMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Orthodontic tooth movement is a biologically mediated process resulting from the application of controlled mechanical forces to teeth. These forces initiate complex cellular and molecular responses within the periodontal ligament and alveolar bone, leading to bone resorption and apposition. Understanding the biological mechanisms underlying orthodontic movement is essential for optimizing treatment efficiency and minimizing complications such as root resorption and periodontal damage. The aim of this study was to analyze the cellular, molecular, and tissue-level responses occurring during orthodontic tooth movement and to evaluate their clinical implications. A literature-based analytical review combined with clinical radiographic observations of 120 orthodontic patients was conducted. The results demonstrate that mechanical stress induces inflammatory mediators, cytokine activation, osteoclast differentiation, and bone remodeling. Controlled force levels promote physiological remodeling, whereas excessive forces result in hyalinization and root resorption. The study confirms that orthodontic movement is a balanced biological response requiring careful force modulation and monitoring.